“EUROWORDS” IN UKRAINIAN WORLD IMAGE DIMENSIONS OF XXI CENTURY (DRAWING ON THE ASSOCIATIVE EXPERIMENT RESULTS) - Bohomolets-Barash, O. (Linguistic and Conceptual Worldviews, 2019)
The ongoing process of European integration in Ukraine determines the significance of the topic of research. The article deals with a phenomenon of a contemporary Ukrainian language known as “Eu- ropean speak” (“Eurospeak”, originally “Euromova”), which involves the use of compound words with a prefix “euro”. Such words, mentioned in the article, are the result of the verbalization of the concept EUROPE. The process of creating these neologisms began in the 90s of the last century since Ukraine gained independence, and continues to this day. For instance, we are talking about such a popular phenomenon as “Eurorepair”, which means ‘high quality, new, better; repair like in Europe’. Researchers indicate that the component “euro” has become a significant “sticker” meaning all (West- ern) European. It can be any household goods, stores, catering, etc. However, in spite of the strong de- sire to “be like in Western Europe”, the quality is not always adequate, and therefore, the researchers draw attention to double standards, partiality and selectivity in the use of similar nominations, which is inherent in the countries of Eastern Europe in general. That is why such words can sound with a certain irony and sarcasm, suggesting the exact opposite. Consequently, Euro-2012 and Euromaidan (2013–2014) became a powerful impulse for the cre- ation and use of Eurospeak, when the media recorded a whole series of innovations with the use of the component “Euro”. Thus, there was a transition in the functioning of these “eurowords” from a purely household spoken sphere to a higher level – to civil and socio-political realities. These particular words mentioned in the article reflect some of the key phenomena of that time. For example, “Euro- piano” is a piano, which was found at Euromaidan and which people played throughout the events of Euromaidan and Revolution of Dignity. In the media, such compound words perform a diﬀerent stylistic function, depending on the author’s plan and have diﬀerent emotional connotations: from negative-oﬀensive to sublime-patriotic. The study is designed to provide an interpretation how young Ukrainians perceive particular ele- ments of the “Eurospeak” nowadays. For this purpose, amongst the students of philology, a Free Associative Experiment was conducted, during which respondents were asked to bring associations on selected “Eurowords”. The results of the survey have confirmed the “European choice” oﬃcially declared by Ukraine. There is reason to believe that modern Ukrainians definitely see their future in Europe, but in Europe, which begins in renewed, up-to-date, European capital of Ukraine – in “Eu- roKyiv”. Perspectives for further research we see in two aspects. Firstly, in the investigation of upcoming neologisms with the component “euro” which will demonstrate common tendencies in the perception of Europe from the Ukrainian side. Secondly, in the diachronic research of the history of Europe con- ceptualization in Ukraine.